G356 Juvenile idiopathic arthritis and other autoimmune diseases in a nationwide paediatric inflammatory bowel disease cohort. (27th April 2015) - Merrick, VM; Henderson, P; Drummond, H; Van Limbergen, J; Russell, RK; Satsangi, J; Wilson, DC
Abstract : Aims: Autoimmune diseases (AIDs) affect up to 10% of individuals living in Europe, so are a significant cause of chronic morbidity. High rates of immune-mediated comorbidity and familial clustering suggest that genetic predisposition underlies AI disease susceptibility, yet few clinical studies have defined the prevalence rates of co-morbid AIDs in specific paediatric populations. This study aims to document the occurrence of Juvenile Idiopathic Arthritis (JIA) and other AIDs in a Scotland-wide cohort of paediatric inflammatory bowel disease (PIBD; diagnosed <17 years of age) patients. Methods: The Paediatric-onset IBD Cohort and Treatment Study (PICTS) is a nationwide Scottish study of incident and prevalent PIBD patients, collecting a wide range of data, including rigorous phenotyping, with continuous long-term follow-up. The PICTS database was interrogated to identify patients enrolled up to 30/06/12 (follow-up to 30/06/14) with a diagnosis of at least one associated AID by last follow-up. Cases believed to be related to use of anti-TNFα treatment were excluded. Results: Of 809 patients in the PICTS cohort, 43 had one or more associated AID, an overall co-morbid immune disease rate of 5.3%; 49% (21/43) male. There were 44 AIDs in 43 patients; one patient had dual AIDs (psoriasis [PSOR] and spondyloarthropathy [SPA]) co-existing with IBD. Otherwise, there were 7 cases of JIA, 3 cases of SPA and 9 cases of PSOR. Additionally there were 4 cases of coeliac disease, 2 of thyroiditis and 2 cases of type 1 diabetes. No cases of Systemic Lupus Erythematosus (SLE) were identified. There were 15 cases of autoimmune liver disease (Primary Sclerosing Cholangitis [PSC], Auto-Immune Hepatitis [AIH] and Autoimmune Sclerosing Cholangitis [ASC]) in this cohort, accounting for 35% of all PIBD-associated AID. Conclusion: Over 5% of PIBD patients in this large cohort study have associated AIDs. Autoimmune liver disease is the commonest AID in this cohort of PIBD patients, followed by PSOR accounting for 23%; JIA accounted for 16% of PIBD-associated AID.